Analisis Kemampuan Berpikir Kreatif Matematika Peserta Didik dalam Menyelesaikan Soal Open-Ended di Kelas VIII SMPN 4 Bukittinggi - Rini Hendri (Jurnal Edukasi dan Penelitian Matematika, 2019)
Creative thinking is the ability in creating various, new, and extraordinary ideas and ways. This ability is one of the skills that is needed to encounter the rapid changing era. In fact, mathematics learning in grade VIII of SMPN 4 Bukittinggi, had not been set creative thinking as the goal. This research aimed to describe students’ creative thinking skills in solving open-ended questions for grade VIII of SMPN 4 Bukittinggi. The research used qualitative method with descriptive research type. The data was collected by observation, questionnaires, mathematical creative thinking skills’ test, and the interview. Based on the results of data analysis, it is found that students' creative thinking abilities are in enough category, with the criteria of each indicator, namely: fluency and flexibility in the enough category, originality and elaboration indicators in good categories.Keywords—Analysis, creative thinking ability, open- ended problem.